Towards Legal Justice: Expanding Criteria for Obligatory Bequests in Unregistered Wives in Polygamous Marriages - Lubis, Rusdi Rizki; Asmuni, Asmuni; Mukharrom, Tamyiz; Seroza, Candra Boy; Kahar, Aisyah (Al-Ahkam, 2025)
Decision Number 183/Pdt.G/2023/PA.Mbl and Number 547/Pdt.G/2023/PA.Utj has paved the way for expanding the implementation of obligatory bequest by granting the inheritance to the unregistered wife in a polygamous marriage. Stepchildren, non-Muslim heirs, and biological children born outside of a registered marriage are forms of expansion of the obligatory bequest regulated in the nomenclature of jurisprudence or the Circular of the Supreme Court (SEMA). This article is qualitative, with a normative and empirical juridical approach to finding legal justice through the path of maqāṣid al-sharī'a. The results of the study show that judges, to realize legal justice, have expanded the implementation of the obligatory bequest by granting the heir's property to the unregistered wife of a polygamous marriage. The researcher offers five criteria for granting an obligatory bequest to the unregistered wife. First, the unregistered polygamous marriage is known to the legally registered wife. Second, the rights and obligations between husband and wife have been implemented. Third, the time of obtaining the inherited property. Fourth, the maximum limit for obtaining inheritance property does not exceed the registered wife's share.  Fifth, the psychological factor between husband and wife has been well established.